Next-generation sequencing applications in food science: fundamentals and recent advances - Joel Tigrero-Vaca; Byron Díaz; Ganyu Gu; Juan Manuel Cevallos-Cevallos (Frontiers in Bioengineering and Biotechnology)
Next-generation sequencing (NGS) has revolutionized food science, offering unprecedented insights into microbial communities, food safety, fermentation, and product authenticity. NGS techniques, including metagenetics, metagenomics, and metatranscriptomics, enable culture-independent pathogen detection, antimicrobial resistance surveillance, and detailed microbial profiling, significantly improving food safety monitoring and outbreak prevention. In food fermentation, NGS has enhanced our understanding of microbial interactions, flavor formation, and metabolic pathways, contributing to optimized starter cultures and improved product quality. Furthermore, NGS has become a valuable tool in food authentication and traceability, ensuring product integrity and detecting fraud. Despite its advantages, challenges such as high sequencing costs, data interpretation complexity, and the need for standardized workflows remain. Future research focusing on optimizing real-time sequencing technologies, expanding multi-omics approaches, and addressing regulatory frameworks is suggested to fully harness NGS’s potential in ensuring food safety, quality, and innovation.